Trends and Associated Factors of Under-five Mortality Based on 2008–2016 Data in Kersa Health and Demographic Surveillance Site, Eastern Ethiopia. (31st March 2022) - Gutema, Gebisa Dirirsa; Geremew, Abraham; Mengistu, Dechasa Adare; Dammu, Yohannes Mulugeta; Bayu, Kefelegn
Background : Of the 6.2 million estimated deaths of children under 15 years of age globally, the death toll of children under 5 years of age accounted for 5.3 million. In Ethiopia, even though significant progress has been made, facility-based research shows that the mortality rate of children under 5 is still high. In the country, particularly in the eastern part, evidence on trends in under-five mortality and associated factors from population-based longitudinal data is limited.Objective : The objective of the study was to assess under-five mortality focusing on the trends and associated factors based on 2008–2016 data in Kersa Health and Demographic Surveillance Site, Eastern Ethiopia.The method : The study was based on 9 years of surveillance data. The surveillance site was founded in 2007 with the aim of producing community-based health and demographic data in the eastern Ethiopia. Data were collected from the surveillance site and analyzed with STATA version 15 (for factor analysis) and/or Statistical Package for Social Sciences (SPSS) version 26 (for trend analysis) and Microsoft (MS) Excel software. The autoregressive integrated moving average (ARIMA) model and Mann–Kendall were used to analyze mortality trends. Multi-level logistic regression was used to assess the associated factors.Result : There were a total of 18 759 newborns in the surveillance sites, of which 1602 died of children under 5 years of age, and the total mortality rate for children under 5 years of age was 85 per 1000 live births. Trend analysis shows that the mortality rate of children under 5 has been steadily declining during the study period. Multi-level logistic regression shows that the variance of the random component model related to the intercept term is statistically significant, which means that there is a change in the mortality rate of children under 5 between the survey years, which is explained by the random intercept term. Antenatal care visits by mothers (AOR = .61, 95% CI = .49, .74), primary education (AOR = .58, 95% CI = .49, .68), normal birth weight (AOR = .78, 95% CI = .64, .95), and having 2 or fewer total births (AOR = .37, 95% CI = .22, .37) were all associated with child death.Conclusion : Despite the downward trend, the mortality rate of children under 5 years old at the surveillance sites is high. Effective intervention measures should be implemented.